STATUS KEBERLANJUTAN PERIKANAN TANGKAP SKALA KECIL - Maman Hermawan; M. Fedi A. Sondita; Akhmad Fauzi; Daniel R. Monintja (Buletin PSP, 2006)
Fisheries sustainability is determined by several interacting factors such as ecology, technology, social, economic and ethics (including law and institution). Objective of this study is to determine the sustainability status of small capture fisheries in view of ecological, technological, social, economic, and law (including institutional) dimensions. Rapfish, a quantitative analysis technique, is used to assess sustainability status of fisheries in the coastal area of Serang (Banten) and Tegal (Central Java). In Pasauran Serang, jaring udang currently is in sustainable status, while payang bugis is in less sustainable. In contrast, jaring rampus, bundes and payang gemplo in Tegal are not in sustainable status especially for the ecological dimension. At regional scale, the sustainability status of fisheries in Serang is better than the fisheries in Tegal. The study shows that ecological dimension is the weakest dimension in order to manage and promoting small scale fisheries sustainability in Tegal. This study reconfirms the need to apply comprehensive and integrated bio-technico-socioeconomic aspects in developing fisheries management.